Don't blame it on the sunshine! An exploration of the spatial distribution of heat injustice across districts in Antwerp, Belgium. Issue 2 (1st February 2022) - Burbidge, Manon; Smith Larsen, T.; Feder, S.; Yan, S.
ABSTRACT: Cities experience temperature differences during heat events, in part modulated by green spaces. In the face of climate change, vegetation and green infrastructure are increasingly important for residents' thermal comfort. Generally, socio-economically marginalised communities are more likely to live in neighbourhoods with less access to green spaces, which can lead to the experience of hotter temperatures and higher incidences of poor health during heat-waves. Building on three bodies of literature – thermal inequity and green space planning, risk and vulnerability, and critical urban theory – an interdisciplinary approach was employed to understand residents' perceptions of heat and vulnerability, and disparities in distribution of green space arising due to urban planning in Antwerp, Belgium. Using census data, a high and low-vulnerability district – Borgerhout and Wilrijk – were selected as case studies. Park audits and interviews were carried out to provide insights into parks' cooling ability and residents' potential responses to extreme heat. Results demonstrated an unequal distribution, access and quality of green spaces between inner-city Borgerhout and suburban Wilrijk, suggesting that lower-income, vulnerable residents are systematically disadvantaged by municipal green space planning. All Borgerhout interviewees described feeling too hot in summer, whilst the opposite held true for interviewees in Wilrijk. Results were situated within Antwerp planning documents to understand how neoliberalism and social exclusion drive and reproduce patterns of injustice, introducing the term "heat injustice" to describe entrenched injustice in green space distribution and corresponding resident perceptions, experiences of and vulnerabilities to heat within the city.